THE EMERGENCE OF STUDENTS’ METACOGNITION IN THE PROCESS OF MATHEMATICAL PROBLEM SOLVING - Kusumaningtyas, Nopem; Sa'dijah, Cholis; Rahardi, Rustanto; Rahardjo, Swasono (International Journal of Insights for Mathematics Teaching (IJOIMT), 2018)
Developing a problem-solving skill for important things which need to be paid attention is how the students' thinking process in solving a problem is. Thinking about what is thought in this term relates to students' awareness of their ability to develop various ways which may be taken in solving a problem is known as metacognition. The existence of metacognition is very important for students in solving mathematical problems. This is a qualitative study using the grade VII students having medium ability as the subjects. The results of the study obtained that through intervention conducted by the researchers in 5 meetings, metacognition capability emerged in the subjects so that with their own ability they are able to solve mathematical problems provided.